Hydrogenase Mimics in M12L24 Nanospheres to Control Overpotential and Activity in Proton-Reduction Catalysis - Zaffaroni, Riccardo; Orth, Nicole; Ivanovic-Burmazovic, Ivana; Reek, Joost N.H. (Angewandte Chemie, 2020)
Hydrogenase enzymes are excellent proton reduction catalysts and therefore provide clear blueprints for the development of nature-inspired synthetic analogues. Mimicking their catalytic center is straightforward but mimicking the protein matrix around the active site and all its functions remains challenging. Synthetic models lack this precisely controlled second coordination sphere that provides substrate preorganization and catalyst stability and, as a result, their performances are far from those of the natural enzyme. In this contribution, we report a strategy to easily introduce a specific yet customizable second coordination sphere around synthetic hydrogenase models by encapsulation inside M12L24 cages and, at the same time, create a proton-rich nano-environment by co-encapsulation of ammonium salts, effectively providing substrate preorganization and intermediates stabilization. We show that catalyst encapsulation in these nanocages reduces the catalytic overpotential for proton reduction by 250 mV as compared to the uncaged catalyst, while the proton-rich nano-environment created around the catalyst ensures that high catalytic rates are maintained.
CRIS-Team Scopus Importer:2020-08-28
Keywords: catalysis; hydrogenases; proton reduction; substrate preorganization; supramolecular cages